Poeci emigracji rosyjskiej i ich zainteresowanie literaturą polską (rekonesans) - Zienkiewicz, Tadeusz (Acta Polono-Ruthenica, 2008)
The analysis of writing by Russian poets-emigrants used to live in Poland in mid-war period shows, that part of their pieces were inspired by Polish literature. In Russian newspapers and collections of poetry can be found poems, which are translations from Polish literaturę and contain themes from poems by Polish poets. Writers like: D. Bochan, I. Kulisz, K. Olenin. L. Sienicka, G. Sorgonin, J. Wadimow, L. Gomolicki, P. Kolski, S. Koncewicz and others, often reach to Polish poets writings - both old pieces and contemporary. Their interests were often focus on romantic poetry (A. Mickiewicz, J. Słowacki, Z. Krasiński and their poems written during the emigration). The main reason of this particular interests was the resemblance of Polish and Russian emigrants fate.